Pemberdayaan Masyarakat Pesisir dalam Pencegahan Malaria pada Anak di Kampung Turu Wilayah Kerja Puskesmas Serui Kota - Arisjulyanto, Dedy; Mesa, Nofita Dewi Kok; Istyanto, Febry; Siregar, Neny San Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
Malaria remains a significant health issue in the coastal areas of Yapen Islands Regency, particularly among children who are at high risk of morbidity and mortality. To address this, a community empowerment and mentoring activity was conducted in Kampung Turu, the service area of Serui Kota Health Center, with the aim of increasing knowledge and practices related to malaria prevention through a community-based education approach. The program involved 60 respondents and was carried out in three stages: preparation, implementation, and monitoring and evaluation. The interventions included malaria education, demonstrations on the use of insecticide-treated bed nets, environmental management, and training community health workers as education agents. Pre–post test evaluations showed an improvement in community knowledge and awareness regarding malaria prevention in children. The community empowerment approach was proven effective in promoting positive behavioral changes and enhancing the capacity of parents and health workers to carry out sustainable malaria prevention efforts. This program is expected to serve as a model for public health interventions in coastal areas aimed at reducing the risk of malaria in children.